Applying the Debate Method to Improve Speaking Skills (An Experimental Study on Sixth-Grade Students at Ma'had 'Ulūm ad-Dīn). - Muhammad Iqbal; Azman Ismail; Zulhelmi Zulhelmi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The purpose of this study is to know the application of the Debate Method to improve speaking skills for Senior High School Students of class XII -A in Ulumuddin Boarding School Utenkot, Cunda - Lhokseumawe for academic years 2018 – 2019, and to know students' effectivity after applicating the Debat Methode. This research is classroom action research conducted in 3 cycles. Each cycle consists of planning, action, observation/evaluation, and reflection. The subjects of this study are senior high school students of class XII-A who are 25 students and the object of this research is speaking skills. Data collection in this study is carried out by the method of observation, interviews, and diagnostic tests. The data are analyzed by quantitative descriptive and statistical analysis techniques. The results showed (1) that the application of the debate Method consisted of the stages of the purpose of Debate method application in the learning process of teaching Arabic, giving titles, limiting the Debate members, making debating rooms in class, searching for information about the title of the Debate, and providing evaluation sheets activities of researchers and students in the application the Debate method, (2) in the application of the Debate Method there is an increase in the percentage of speaking skills of students of class XI -A MA in terms of pronunciation, fluency, vocabulary, and sentence structure. Based on the results of the analysis in the first cycle, the average student's speaking skills are obtained as much as 70% (